A sustained release of BMP2 in urine-derived stem cells enhances the osteogenic differentiation and the potential of bone regeneration. (25th April 2022) - Wu, Shuang; Chen, Zhao; Yu, Xi; Duan, Xin; Chen, Jialei; Liu, Guoming; Gong, Min; Xing, Fei; Sun, Jiachen; Huang, Shishu; Xiang, Zhou
Abstract: Cell-based tissue engineering is one of the optimistic approaches to replace current treatments for bone defects. Urine-derived stem cells (USCs) are obtained non-invasively and become one of the promising seed cells for bone regeneration. An injectable BMP2-releasing chitosan microspheres/type I collagen hydrogel (BMP2-CSM/Col I hydrogel) was fabricated. USCs proliferated in a time-dependent fashion, spread with good extension and interconnected with each other in different hydrogels both for 2D and 3D models. BMP2 was released in a sustained mode for more than 28 days. Sustained-released BMP2 increased the ALP activities and mineral depositions of USCs in 2D culture, and enhanced the expression of osteogenic genes and proteins in 3D culture. In vivo, the mixture of USCs and BMP2-CSM/Col I hydrogels effectively enhanced bone regeneration, and the ratio of new bone volume to total bone volume was 38% after 8 weeks of implantation. Our results suggested that BMP2-CSM/Col I hydrogels promoted osteogenic differentiation of USCs in 2D and 3D culture in vitro and USCs provided a promising cell source for bone tissue engineering in vivo . As such, USCs-seeded hydrogel scaffolds are regarded as an alternative approach in the repair of bone defects. Graphical Abstract: